Games-based learning advancements for multi-sensory human computer interfaces [ techniques and effective practices - Boyle, Liz; Connolly, Thomas M.; Stansfield, Mark , 1963- (Information Science Reference, 2009)
"This book provides an extensive treatment of the field of games-based learning, providing a presentation of what we know about the subject, where the key challenges lie, and some of the approaches to addressing these key challenges"--Provided by publis